A Metabolic Trade-Off Modulates Policing of Social Cheaters in Populations of Pseudomonas aeruginosa - Yan, Huicong; Wang, Meizhen; Sun, Feng; Dandekar, Ajai A.; Shen, Dongsheng; Li, Na (Frontiers in Microbiology, 2018)
Pseudomonas aeruginosa uses quorum sensing (QS) to regulate the production of public goods such as the secreted protease elastase. P. aeruginosa requires the LasI-LasR QS circuit to induce elastase and enable growth on casein as the sole carbon and energy source. The LasI-LasR system also induces a second quorum-sensing circuit, the RhlI-RhlR system. During growth on casein, LasR-mutant social cheaters emerge, and this can lead to a population collapse. In a minimal medium containing ammonium sulfate as a nitrogen source populations do not collapse, cheaters and cooperators reach a stable equilibrium; however, without ammonium sulfate, cheaters overtake the cooperators and populations collapse. We show that ammonium sulfate enhances activity of the RhlI-RhlR system in casein medium and this leads to increased production of cyanide, which serves to control levels of cheaters. This enhancement of cyanide production occurs because of a trade-off in the metabolism of glycine: exogenous ammonium ion inhibits the transformation of glycine to 5,10-methylenetetrahydrofolate (5,10-methylene-THF) through a reduction in expression of the glycine cleavage genes gcvP1 and gcvP2, thereby increasing the availability of glycine as a substrate for RhlR-regulated hydrogen cyanide synthesis. Thus, environmental ammonia enhances cyanide production and stabilizes QS in populations of P. aeruginosa.